Perbedaan Kecepatan Berjalan Penggunaan Rigid Medial Arch Support dengan Flexible Medial Arch Support pada Penderita Flat Foot - Atika Febri Anggriani; Yopi Harwinanda Ardesa; Prasetyo Catur Utomo (Jurnal Keterapian Fisik, 2020)
Background: Flat foot is a clinical orthopedic condition that occurs when the medial longitudinal arc does not appear from birth, this condition can cause complaints of fatigue and restrict walking activities. Handling of flat foot in the prosthetic orthotic field is by the use of medial arch support that can be made with various types of designs and materials. In terms of orthosis type material can be either rigid medial arch support and flexible medial arch support that can be used to correct flatfoot conditions. The purpose of this study was to determine whether there were differences in walking speed with the use of rigid medial arch support and flexible medial arch support in patients with flat foot. Methods: This type of research is Observational with Cross Sectional design. The samples used were children aged 8-12 years totaling 20 samples of boys and girls, grades 4 through 6 Elementary School, with body weights of 26-60 kg, and height of 124-150 cm. The results of calculating the average walking speed using rigid medial arch support is 0.69 m / s and the average result of walking speed calculation using flexible medial arch support is 0.78 m / s. Results: The results of Shapiro Wilk data normality (N = 20) show that the data is not normally distributed. So by using the non parametric test (Wilcoxon test) obtained P = 0,000 (P <0.05). Conslusion: ConFrom the test results it can be concluded that there are differences in the speed of walking using rigid medial arch support with flexible medial arch support in patients with flat foot. This is because the use of medial arch support with flexible material can be used to support the arch to stay awake. While the use of rigid medial arch support is stiffer and less able to adjust foot movements, especially when walking.